Karakteristik dan Daya Hambat Mikroba Edible Film dengan Penambahan Filler Kulit Salak (Salacca zalacca) sebagai Pengemas Makanan - Dalimunthe, Nisaul Fadilah; M. Thoriq Al Fath; S. Ginting, M. Hendra; Natasya, Tania; Pulungan, Khairunnisa Alifia (Jurnal Teknik Kimia USU, 2023)
An edible film serves to protect and improve food quality. One of the ingredients that can be used is pectin. However, edible films made from pectin have fragile mechanical properties, so snakefruit peel is added as a filler to improve mechanical properties. Edible films were prepared with concentrations from 0%, 2%, 3%, 4%, and 6% (wt), pectin, glycerol (C3H8O3), calcium hloride dihydrate (CaCl2.2H2O) and Tween 80. It was stirred with magnetic stirrer, printed and dried in an oven to test the properties. As a result, the addition of snakefruit peel affected the thickness, swelling, degradation and antimicrobial. The thickness obtained is between 0.024 mm - 0.0172 mm. The swelling results obtained ranged from 0.0409 - 0.0137. The best degradation results were obtained on day 5th, with varying concentrations of 6% snakefruit peel. The results of the study on antimicrobial activity showed that maximal inhibition with varying concentrations of 6% snakefruit peel with an inhibition zone of 20.8 mm.